2011
DOI: 10.1024/1662-9647/a000048
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Cognitive Function after Physical Movement Training in Institutionalized Very Frail Older Adults with Dementia

Abstract: Abstract. Physical exercise has positive effects on cognitive functioning in both healthy older adults and ambulatory older adults with dementia. The present study investigated whether a 10-week multimodal movement intervention conducted in the seated position can slow cognitive deterioration in demented and physically very frail nursing-home residents. Our analysis revealed that training participants showed no further overall cognitive deterioration throughout the study and a significant improvement in the AD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 35 publications
0
35
0
1
Order By: Relevance
“…Consequently, many studies in the elderly have shown that improving aerobic capacities through physical exercise programs has beneficial effects on cognitive performance (Kramer et al, 1999; Deley et al, 2007; Sumic et al, 2007; Hillman et al, 2008) and that physical activity can even reduce the likelihood of developing cognitive impairments (Kramer et al, 2006; Thurm et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, many studies in the elderly have shown that improving aerobic capacities through physical exercise programs has beneficial effects on cognitive performance (Kramer et al, 1999; Deley et al, 2007; Sumic et al, 2007; Hillman et al, 2008) and that physical activity can even reduce the likelihood of developing cognitive impairments (Kramer et al, 2006; Thurm et al, 2011). …”
Section: Discussionmentioning
confidence: 99%
“…The intervention is specifically developed for this study based on theoretical considerations, results of a pilot study [ 47 ], and a literature review [ 48 ]. The combination of motor and cognitive tasks used in the MEP aims to enhance the effectiveness of physical activity on cognition.…”
Section: Methodsmentioning
confidence: 99%
“…For the physical training program, we used a multimodal training regime based on a program that has previously been shown to have cognitive benefits (Thurm et al, 2011). The use of a multimodal exercise program is consistent with findings of larger cognitive benefits through combined aerobic and strength training versus aerobic exercise only (Colcombe et al, 2006; Smith et al, 2010).…”
Section: Introductionmentioning
confidence: 99%